Protective efficacy of individual CD8+ T cell specificities in chronic viral infection - Johnson, Susan; Graw, Frederik (The journal of immunology, 2015)
Specific CD8+ T cells (CTLs) play an important role in resolving protracted infection with hepatitis B and C virus in humans and lymphocytic choriomeningitis virus (LCMV) in mice. The contribution of individual CTL specificities to chronic virus control, as well as epitope-specific patterns in timing and persistence of antiviral selection pressure, remain, however, incompletely defined. To monitor and characterize the antiviral efficacy of individual CTL specificities throughout the course of chronic infection, we coinoculated mice with a mixture of wild-type LCMV and genetically engineered CTL epitope-deficient mutant virus. A quantitative longitudinal assessment of viral competition revealed that mice continuously exerted CTL selection pressure on the persisting virus population. The timing of selection pressure characterized individual epitope specificities, and its magnitude varied considerably between individual mice. This longitudinal assessment of “antiviral efficacy” provides a novel parameter to characterize CTL responses in chronic viral infection. It demonstrates remarkable perseverance of all antiviral CTL specificities studied, thus raising hope for therapeutic vaccination in the treatment of persistent viral diseases.
Im Titel ist das Pluszeichen hochgestellt
Gesehen am 09.06.2020